2020
DOI: 10.1016/j.annonc.2020.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab emtansine (T-DM1) in patients with HER2-positive metastatic breast cancer and brain metastases: exploratory final analysis of cohort 1 from KAMILLA, a single-arm phase IIIb clinical trial☆

Abstract: Background: Patients with brain metastases (BM) from human epidermal growth factor receptor 2 (HER2)-positive breast cancer represent a difficult-to-treat population. Trastuzumab emtansine (T-DM1) has shown potential activity in this subset of patients in small clinical series. Patients and methods: KAMILLA is an ongoing, phase IIIb study of T-DM1 in patients with HER2-positive locally advanced/metastatic breast cancer with prior HER2-targeted therapy and chemotherapy. Patients received T-DM1 3.6 mg/kg every 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
175
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(206 citation statements)
references
References 32 publications
(22 reference statements)
4
175
2
6
Order By: Relevance
“…69 A subgroup analysis of 398 patients with BM included in the KAMILLA single-arm open-label, Phase 3b study published in 2020, confirms the efficacy and safety of T-DM1 in this situation, with a BM response rate of 21%, a median PFS of 6 months and a median OS of 19 months. 70 Pertuzumab-trastuzumab combination for patients with HER2 + BM. Pertuzumab is a recombinant humanised monoclonal antibody targeting the dimerisation domain II of HER2 that was approved for the first-line treatment of patients with HER2 + MBC following the randomised Phase 3 placebo-controlled CLEOPATRA trial.…”
Section: Trastuzumab-based Regimens For Patients With Her2 + Bmmentioning
confidence: 99%
“…69 A subgroup analysis of 398 patients with BM included in the KAMILLA single-arm open-label, Phase 3b study published in 2020, confirms the efficacy and safety of T-DM1 in this situation, with a BM response rate of 21%, a median PFS of 6 months and a median OS of 19 months. 70 Pertuzumab-trastuzumab combination for patients with HER2 + BM. Pertuzumab is a recombinant humanised monoclonal antibody targeting the dimerisation domain II of HER2 that was approved for the first-line treatment of patients with HER2 + MBC following the randomised Phase 3 placebo-controlled CLEOPATRA trial.…”
Section: Trastuzumab-based Regimens For Patients With Her2 + Bmmentioning
confidence: 99%
“…8 TDM1(Trastuzumab emtansine) has shown to be active in HER2-positive breast cancer patients with brain metasta-sis from the phase III KAMILLA trial. 13 Another HER2-ADC, RC48-ADC, has been carried out in phase II trials and demonstrated a clinically meaningful overall response rate (ORR) in pretreated HER2-positivie urothelial carcinoma patients. 15 Although these agents/combinations provide supporting evidence for further investigation in HER2-positivie GC, the response rate of HER2-positive patients received HER2-targeted therapy remain limited, and the frequently upcoming resistance is another reason that impaired therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its tight regulation to crucial downstream signaling nodes such as RAS/RAF/MYC and PI3K‐Akt, HER2 remains to be the prior choice of targeted drug development for patients with advanced GC 5 . To date, a variety of HER2‐targeted drugs has been developed and evaluated by clinical trials separately and combined, including HER2 antibody and its derivatives (Trastuzumab and Pertuzumab), tyrosine kinase inhibitor (Lapatinib, Neratinib, and Afatinib), and antibody‐drug conjugates (ADCs) (DS‐8201a, TDM1, and RC48) 6–13 . Monoclonal antibody Trastuzumab is the only HER2‐targeted agent currently approved for first‐line practice of GC 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations